SWOT Analysis of Marketing Strategies on Services in Islamic Financial Institutions (Case Study at KJKS (Sharia Financial Services Cooperative) BMT La Tansa Gontor Ponorogo) - Fahmi, Annas Syams Rizal; Muqorobin, Ahmad (AL-IKTISAB: Journal of Islamic Economic Law, 2020)
Service is a form of marketing strategy in a company. In this case, many conventional financial institutions and Islamic financial institutions are competing in improving the quality of service to be provided to customers and potential customers. BMT La Tansa Gontor is one of the sharia financial institutions under the Sharia Financial Services Cooperative (KJKS) that try to give a solution on community’s economic difficulties with the values of Islam by publishing murabahah financing products. In this study, the author will discuss how the marketing strategies that have been carried out by BMT La Tansa Gontor in terms of service. This research will use the SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis to find the extent of the services provided by BMT La Tansa and will provide conclusions about what BMT La Tansa should do after this research is complete. Marketing strategy that have been carried out by BMT La Tansa Gontor for customers is by giving services that have Gontor characteristics and characteristics namely, friendly service, comfortable communication based on kinship, the mechanism process in product purchasing procedures that is very comfortable to make customers loyal to BMT La Tansa Gontor, the staff’s persuasive method apart from being young but also with a good appearance is its own attraction. The results of analysis and observation using SWOT, the researcher concluded that BMT La Tansa Gontor has some weaknesses, one of the factors were the lack of structured regeneration so that the pattern of value transformation and learning from seniors to juniors experienced difficulties and researchers could provide input that the strategy marketing that must be done by the BMT La Tansa Gontor in service to customers is to use SO (Strength-Oppoturnity) combined with ST (Strength-Threath) which is to take advantage of opportunities with existing strengths to be able to face threats from outside parties.